Absolute Superman. Vol. 1, Last dust of Krypton - Aaron, Jason; Siegel, Jerry, 1914-1996; Shuster, Joe, 1914-1992 (DC Comics, 2025)
"Without the fortress, without the family, without a home...what's left is the Absolute Man of Steel! Spiraling out of the catastrophic events of Absolute Power, a new side of the DC Universe is born--the Absolute Universe! In a different, darker world, Kal-El landed in a remote Kansas field, the last survivor from an alien planet...but even before that moment, nothing unfolded as you'd expect. As he tries to survive in a world seemingly determined to repeat the mistakes of the demolished Krypton, he'll come into conflict with the globe-straddling Lazarus Corporation and its agenda of exploitation...and go fist-to-fist with its brutal army of Peacemakers!"--Amazon.com.